Hezbollah as a norm entrepreneur: Reconstructing resistance and legitimacy - Elbenhawy, Ali (AUC Knowledge Fountain, 2016)
Using social constructivism, this research analyzes Hezbollah as a norm entrepreneur in the Middle East. My research question is: How does Hezbollah function as a norm entrepreneur in the Middle East or how does Hezbollah create the norm of resistance? Material resistance is created through institutionalized ideas, such as jihad, martyrdom, the oppressed/oppressor dichotomy, and anti-imperialism. Special attention is given to the shifts in Hezbollah’s ideology. These ideas were physically expressed in the 2006 war with Israel and currently in Syria. However, since Hezbollah’s involvement in Syria, Hezbollah’s norm of resistance has waned. Its alternative definition of resistance is not accepted by many across the region who perceive Hezbollah as a puppet of an oppressive regime. The popularity and legitimacy Hezbollah enjoyed following its “Divine Victory” in 2006 has since been jeopardized in favour of rescuing the resistance bloc and resisting what it constructs as a plot to re-make the Middle East.